Logistics Service Quality and Customer Satisfaction: Evidence from Salalah Port Oman - Sukati, Inda; Husda, Nur Elfi; Wangdra, Yvonne; ., Suhardi; ., Realize (Journal of Ecohumanism, 2024)
Objective: This study aims to explore the influence of the dimensions of service quality provided by Port of Salalah on customer satisfaction. Design/methodology/approach: The study modifies the SERVQUAL model to examine service quality dimensions in the Port setting with five dimensions namely tangibles, empathy, reliability, responsiveness and assurance (TERRA) requirements. The data were collected based on a sample of 300 Salalah Port customers from the administrators that provided logistics services in ports through a questionnaire and analyzed using SPSS. Research Findings: In the case of Port of Salalah, all five dimensions of service quality have a significant and positive impact on Salah Port customer satisfaction. Practical implications: This paper contributes to the existing literature by offering empirical findings. It highlights the important role of service quality; especially reliability in influencing customer satisfaction in this context. The results provide some useful references for port managers to improve the level of service quality and customer satisfaction as a means to strengthen competitiveness.